Reports from the Field: Continuity Education in Emergency and Conflict Situations: The Case For Using Open, Distance and Flexible Learning - Charlotte Creed (Commonwealth of Learning, 2014)
Emergency and conflict in countries such as Syria, the Philippines, Sri Lanka and Afghanistan have made us more aware of the long-term serial disruption and psychosocial damage faced by people caught up in emergency and conflict areas. Open, distance and flexible learning (ODFL) has sometimes been employed in these regions to maintain a degree of continuity in education. For the most part, however, this role has been ad hoc, short-term and often bearing limited relation to the psychosocial and educational needs of the displaced or traumatised populations it serves.